Conserving the European Bonelli's eagle in spatiotemporal domain: Lesson from its feeding pattern. Issue 5 (2nd August 2021) - Upadhyay, Ranjit Kumar
Abstract: Bonelli's eagle ( Hieraaetus fasciatus ), a threatened species in Western Europe, has suffered a critical and severe decline in last two decades. In this article, a qualitative analysis of an ecoepidemiological model which consists of two prey and a predator is carried out. We proposed and designed a spatiotemporal model to predict the distribution of a territorial predator, Bonelli's eagle and its two main prey species (rabbit and red‐legged partridge). Bounded positive solution, feasibility of the equilibria, and their stability analysis are determined for the nonspatial counterpart of the system. Criteria for diffusion‐driven instability caused by local random movements of rabbits, partridges, and Bonelli's eagle are obtained. Possible implications of the result for Bonelli's eagle conservation are discussed. We show that the inclusion of second prey in the system can drastically change the dynamics from the single prey case. We also found that the presence of a second prey is beneficial for the conservation of the threatened Bonelli's eagle population in Europe. Results obtained from theoretical analysis of the nonspatial model agree very well with the numerical simulation results. Lastly, via numerical simulation, we illustrate the effect of diffusion of the dynamical system in the spatial/spatiotemporal domain by different pattern formations.